Support of Road Freight Transport Especially in North-East Part of Schengen Borders - Hricová, Romana (American Journal of Trade and Policy, 2015)
Green logistics is very attractive and request the point of view. Many companies try to be “green”, but on the other hand they also must be quick, be in right time in the right place and everything with as low costs as possible. So because of it, they use more road freight transport. Nowadays road freight transport is much expanded as transport companies prefer the possibility to operate just-in-time.  There are several advantages that give road freight transport the first place. Firstly, the truck can be prepared whenever, no matter what time is chosen.  Secondly, the flexibility and no more borders with customs control inside the Schengen Area make freight transport quicker. On the other hand, innovative approaches ask for environmental protection, which becomes one of the most important points of view.  If countries support this environmental friendly transport, this would be reflected in the transport prices which should make rail transport more interesting. Using the methodology in the manuscript was divided to three steps. The first step is to identify relevant questions related to border crossing. Next step is to elaborate a list of border problems, and the last step is an analysis of available data.
Keywords: logistics; transport; freight; railway; road; Schengen borders; infrastructure